River Basin Management for Optimum Water Yield - Adejuwon, J.O (Obafemi Awolowo University Press, 2013)
In the course of this lecture, I intend to outline a set of procedures for refining the well known generalized concept of a river basin into an empirical, predictive model that could 'be manipulated for the purpose of optimizing water yield. As a major objective, this lecture is directed at modelling the river basin for optimum water yield.